His, Hers, or Ours: Impacts of a Training and Asset Transfer Programme on Intra-Household Decision-Making in Zambia. Issue 9 (2nd September 2019) - Kafle, Kashi; Michelson, Hope; Winter-Nelson, Alex
Abstract: This paper studies the effects of a multifaceted asset transfer programme on the decision-making dynamics of smallholder households. Constructing separate indexes of participation in household decision-making for adult females and males, and using difference-in-differences to assess the impact of livestock transfer and training, we find evidence that these interventions increased the share of decisions in which individuals participated, regardless of gender. Increases in decision-making participation by both men and women are driven by an increase in joint decision-making within the household on the extensive margin. Decisions made jointly by men and women increased by 16 per cent across all household activities, with statistically significant declines in independent decision-making by men and women. Findings are encouraging given the evidence of welfare gains associated both with increases in participation in decision-making by women as well as increased cooperation within households.